2017
DOI: 10.1186/s12871-017-0300-z
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal magnesium sulfate does not reduce the ED50 of intrathecal hyperbaric bupivacaine for cesarean delivery in healthy parturients: a prospective, double blinded, randomized dose-response trial using the sequential allocation method

Abstract: BackgroundAddition of intrathecal magnesium sulfate to local anesthetics has been reported to potentiate spinal anesthesia and prolong analgesia in parturients. The current study was to determine whether intrathecal magnesium sulfate would reduce the dose of hyperbaric bupivacaine in spinal anesthesia with bupivacaine and sufentanil for cesarean delivery.MethodsSixty healthy parturients undergoing scheduled cesarean delivery were randomly assigned to receive spinal anesthesia with 0.5% hyperbaric bupivacaine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 40 publications
1
28
0
Order By: Relevance
“…[ 11 ] Our previous study indicated that the ED 50 values of intrathecal hyperbaric bupivacaine (along with 5 μg sufentanil) with or without magnesium sulfate were 4.9 or 4.7 mg, respectively, in cesarean section. [ 12 ] These results were similar to those seen in this study. However, in a dose–response study conducted by Ginosar et al, the ED 50 of intrathecal hyperbaric bupivacaine (mixed with morphine 200 μg and fentanyl 10 μg) was 7.6 mg in cesarean section.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…[ 11 ] Our previous study indicated that the ED 50 values of intrathecal hyperbaric bupivacaine (along with 5 μg sufentanil) with or without magnesium sulfate were 4.9 or 4.7 mg, respectively, in cesarean section. [ 12 ] These results were similar to those seen in this study. However, in a dose–response study conducted by Ginosar et al, the ED 50 of intrathecal hyperbaric bupivacaine (mixed with morphine 200 μg and fentanyl 10 μg) was 7.6 mg in cesarean section.…”
Section: Discussionsupporting
confidence: 92%
“…According to Tyagi et al [ 11 ] and our prior study, [ 12 ] the sample size is regarded as adequate once 6 pairs of reversals of sequence are achieved when using the up-down method to determine the ED 50 of intrathecal bupivacaine. Each group achieved more than 6 pairs of reversals of sequence after 30 patients enrolled in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The onset time and dose of LOC was also studied. According to Tyagi and our previous study, a sample size of 30 patients for each group was determined in the current study, because sample size is regarded as adequate when 6 pairs of reversal of sequence are achieved [5,6]. The Dixon and Massey formula was applied to calculate the EC50 for both groups [7].…”
Section: Methodsmentioning
confidence: 99%
“…An effective dose was defined as a bilateral T5 or higher sensory block achieved within 10 minutes of intrathecal drug administration without the need for epidural supplementation. 11 In the event of insufficient sensory block, 5-mL bolus doses of 2% lidocaine separated by 5-minute intervals were administrated via the epidural catheter until achieving adequate anesthesia.…”
Section: Study Protocolmentioning
confidence: 99%